TOXICOLOGICAL STUDIES OF “CHONDROKOLA ROSH”, AN AYURVEDIC PREPARATION ON LIVER FUNCTION TESTS OF RATS - Nasrin, Sweety; Bachar, S C; Choudhuri, M S K (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Chondrokola Rosh (CKR) is a traditional metallic Ayurvedic preparation widely used by the rural and ethnic people of Bangladesh in dysuria. It is a preparation of various roasted metals (Hg and Cu), non-metal (sulphur and Mica) and medicinal herbs. Considering the controversy over the risk of toxic heavy metals in Ayurvedic herbo-mineral preparations, toxicological parameters on liver functions were investigated. A single dose of 100mg/kg body weight of the preparation was administered orally to the rats of both sexes for ninety days. In this evaluation a statistically significant (p<0.001) increase of serum albumin levels in male (17%) and female (15%) rat groups were observed. On the other hand, the plasma bilirubin level was decreased 50% and 28% respectively in both rats groups. But no remarkable differences were observed in plasma protein, sGPT, sGOT and ALP activities from their corresponding control values. This study showed that CKR had no remarkable toxic effect on liver of the animals despite the presence of traces of transformed heavy metals.